A APPLICATION OF CONTEXTUAL TEACHING AND LEARNING MODEL IN AL-QUR'AN HADITH SUBJECT FOR DAILY LIFE HABITS -DAILY LIFE OF STUDENTS IN CLASS VIII C OF MTS WALI SONGO PUTRA NGABAR PONOROGO IN THE 2024/2025 ACADEMIC YEAR: PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING - Mustofa, Muhammad Hanif (Muara Aksara: Jurnal Ilmiah Multidisipliner, 2025)
Education is a planned effort to create an environment that supports the learning process and the development of students' potential. It can be seen in the learning of the Qur'an and Hadith, conventional learning is still often carried out, resulting in a lack of understanding and daily habits. Thus, educators choose the Contextual Teaching and Learning model as an effort to instill habits that are in accordance with the material of the Qur'an and Hadith in daily life. The objectives of this study include to determine the planning of the learning model, its application, and the factors of Contextual Teaching and Learning. This study uses a qualitative approach with a case study type of research. The results of the study show that: 1) In the process of planning Contextual Teaching and Learning, educators are expected to prepare a syllabus and lesson plan (RPP) as a reference for learning. 2) The process of implementing the Contextual Teaching and Learning model involves educators delivering material by providing relevant examples and encouraging all students to implement these examples in their daily lives. 3) Supporting factors for the implementation of Contextual Teaching and Learning include high motivation among students and an active learning atmosphere. Meanwhile, the inhibiting factors are that educators rarely attend training workshops and students rarely attend classes, thereby slowing down the implementation of this model.